Analysis of the use of variable speed drives in water supply systems - Nunes, Pedro Daniel da Cunha Moreira (2021)
Currently, operational control at the pumping stations is based on the water levels present in the tanks, ie, each time the water level reaches a certain minimum value, the pumps switch on until the tank is full again. Although this type of control is quite effective, it is also quite inefficient. This type of operation can be largely optimized by adjusting pumping operations to energy prices that vary throughout the day. Additionally, the use of variable speed drives can also increase the efficiency of the pumps due to its adaptations to daily water consumption. However, this type of operation imposes several challenges such as (i) the high difficulty of the operator to accurately predict water consumption patterns every day and for all types of consumers by intuition ; (ii) associate water needs with fluctuations in energy tariffs and with low storage capacity of reservoirs; (iii) know the ideal frequency to pump the water with the lowest energy consumption and (iv) know the equipment used, which, over time, its efficiency decreases substantially. With complex and large systems (such as water supply systems), the attempt to improve operational efficiency can be a "shot in the dark", which can lead to serious implications on the minimum requirements required by final consumers (such as pressures or security of supply). In this thematic area, the goal of this work is to contribute to an increase in the efficiency of these systems. Different studies results are described in the literature, studies concerning the application of VSDs. However, even though they show good results when it comes to energy savings, there is still doubt among the community on the advantages of applying the VSDs, and above all there is still a lack of information on how to use the VSDs. The main goal of this study is to present the benefits of using VSDs, as well as explaining its application. Python simulations were developed with different scenarios for a water distribution network, using VSDs and pumps, even at parallel use. The results achieved were satisfactory and present values of energy savings within expectations.